Highlights of Strategies Targeting Fibroblasts for Novel Therapies for Rheumatoid Arthritis - Chu, Cong-Qiu (Frontiers in Medicine, 2022)
Synovial fibroblasts of rheumatoid arthritis (RA) play a critical role in perpetuation of chronic inflammation by interaction with immune and inflammatory cells and in cartilage and bone invasion, but current therapies for RA are not directly targeted fibroblasts. Selectively fibroblast targeted therapy has been hampered because of lack of fibroblast specific molecular signature. Recent advancement in technology enabled us to gain insightful information concerning RA synovial fibroblast subpopulations and functions. Exploring fibroblast targeted therapies have been focused on inducing cell death via fibroblast associated proteins; interrupting fibroblast binding to matrix protein; blocking intercellular signaling between fibroblasts and endothelial cells; inhibiting fibroblast proliferation and invasion; promoting cell apoptosis and inducing cellular senescence, and modulating fibroblast glucose metabolism. Translation into clinical studies of these fibroblast targeted strategies is required for evaluation for their clinical application, in particular for combination therapy with current immune component targeted therapies. Here, several strategies of fibroblast targeted therapy are highlighted.